Prospective non-interventional BELOVA/BGOG-ov16 study on safety of frontline bevacizumab in elderly patients with FIGO stage IV ovarian cancer: a study of the Belgian and Luxembourg Gynaecological Oncology Group. Issue 6 (21st January 2022) - Vergote, Ignace; Van Nieuwenhuysen, Els; De Waele, Stefanie; Vulsteke, Christof; Lamot, Caroline; Van den Bulck, Heidi; Claes, Nele; Graas, Marie-Pascale; Debrock, Guy; Spoormans, Isabelle; Vuylsteke, Peter; Honhon, Brigitte; et al.
Abstract : Objective: Because elderly patients with ovarian cancer are underrepresented in randomized studies, this study aimed to expand our knowledge on the safety and effectiveness of frontline treatment with bevacizumab in combination with standard carboplatin and paclitaxel chemotherapy in patients aged 70 years and older with a diagnosis of Federation of Gynecology and Obstetrics (FIGO) stage IV ovarian cancer in routine clinical practice in Belgium. Methods: Patients aged 70 years and older with FIGO stage IV ovarian cancer were included in a multicenter, non-interventional prospective study to evaluate the safety and effectiveness of treatment with bevacizumab in combination with frontline carboplatin and paclitaxel chemotherapy. Comprehensive geriatric assessments were performed at baseline and during treatment. Results: The most frequently reported adverse events for bevacizumab were hypertension (55%), epistaxis (32%) and proteinuria (21%). The Kaplan-Meier estimate of progression-free survival was 14.5 months. The results of the comprehensive geriatric assessments during treatment indicated a slight improvement in the geriatric eight health status screening tool score for general health status and the mini-nutritional assessment score for nutritional status. The median change from baseline score was close to zero for the instruments measuring independency, activity of daily living and instrumental activities of daily living, and for the mobility-tiredness test measuring self-perceived fatigue. Conclusions: No new safety signals were registered in this study in patients aged 70 years and older treated with bevacizumab and frontline carboplatin and paclitaxel for FIGO stage IV ovarian cancer. Elderly patients should not be excluded from treatment for advanced ovarian cancer based on age alone. EU PAS register: ENCEPP/SDPP/13849. ClinicalTrials.gov identifier: NCT02393898 .